Encefalites virais em aves silvestres - Lais Talita Souza Hanna (2023)
Brazil is a country with an extensive territorial area made up of different biomes, which allows for a diversity of habitats and wild avian species. Human activity in agriculture, animal production, urbanization, mining, results in a negative impact on environmental homeostasis, with interspecific circulation of etiologies that may be zoonotic, with potential risk to One Health, in addition, losses of wild specimens. Among the relevant diseases, it is important to highlight those involving the Central Nervous System (CNS), since they are generally causes of death in young animals, impacting the wildlife conservation. Diagnostic methods are essential to determine the etiologies of those diseases, allowing the elaboration of prevention and control strategies. The general objective of this study was to analyze the routine casuistry of the Laboratory of Avian Diseases of the Veterinary School – UFMG, of wild avian species necropsied between 2018 and 2022 from greater Belo Horizonte, in addition to investigating viral etiologies of importance for the CNS in samples collected at a conservationist breeding located in Ribeirão das Neves-MG. Were selected sixty-one cases of avian morbid cases, from different orders and families, with a history of clinical neurological signs and/or neurological alterations observed at necropsy. In addition, samples of whole blood, cloacal and tracheal swabs of 18 avian species of normal clinical appearance, captive in a conservationist breeding in Ribeirão das Neves, were collected in 2022. Biological materials and/or CNS fragments from each animal were analyzed for the etiologies of equine encephalitis West Nile virus (WNV), Venezuelan equine encephalitis (VEEV), eastern (EEEV), western (WEEV), Influenza A, avian bornavirus (ABV), Newcastle disease (NDV), Pacheco's disease (PDV), Marek's disease (MDV), avian adenovirus. Among the 61 animals, influenza A was detected using RT-qPCR and RT-PCR techniques, avian bornavirus, pan-herpesvirus in addition to Marek's disease virus and also Pacheco's disease virus (PsHV-1). Among the 18 animals, positivity for influenza A virus was observed in the tracheal swab and for ABV in the cloacal swab. Finally, a blue parrot (Amazona aestiva) with clinical signs compatible with hydrocephalus was analyzed, with anatomopathological and histopathological evaluations indicative of an inflammatory process and analyzes in molecular techniques of negative diagnosis for viral etiologies.